Pengaruh Komponen Modal Kerja terhadap Profitabilitas Perusahaan Manufaktur yang Terdaftar di BEI - Resky Amelia Syafitri; Seto Sulaksono Adi Wibowo (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2016)
This study aimed to analyze the effect of working capital on the profitability. Component of working capital in this study was measured with a receivable turnover ratio, working capital turnover ratio, inventory turnover ratio, and total asset turnover ratio. The profitability in this study was measured using the Return on Assets. This study using purposive sampling for sampling and using 16 food and beverage in 2010-2014 in the Indonesia Stock Exchange. This study uses Eviews version 7.0. The results of this study shows that receivable turnover ratio has no significant effect on the return on assets, working capital turnover ratio has significant positive effect on return on assets, inventory turnover ratio has no significant effect on return on assets, and total assets turnover ratio has a significant positive effect on return on assets.